Developmental and aging resting functional magnetic resonance imaging brain state adaptations in adolescents and adults: A large N (>47K) study. Issue 6 (11th January 2023) - Abrol, Anees; Fu, Zening; Du, Yuhui; Wilson, Tony W.; Wang, Yu‐Ping; Stephen, Julia M.; Calhoun, Vince D.
Abstract: The brain's functional architecture and organization undergo continual development and modification throughout adolescence. While it is well known that multiple factors govern brain maturation, the constantly evolving patterns of time‐resolved functional connectivity are still unclear and understudied. We systematically evaluated over 47, 000 youth and adult brains to bridge this gap, highlighting replicable time‐resolved developmental and aging functional brain patterns. The largest difference between the two life stages was captured in a brain state that indicated coherent strengthening and modularization of functional coupling within the auditory, visual, and motor subdomains, supplemented by anticorrelation with other subdomains in adults. This distinctive pattern, which we replicated in independent data, was consistently less modular or absent in children and presented a negative association with age in adults, thus indicating an overall inverted U‐shaped trajectory. This indicates greater synchrony, strengthening, modularization, and integration of the brain's functional connections beyond adolescence, and gradual decline of this pattern during the healthy aging process. We also found evidence that the developmental changes may also bring along a departure from the canonical static functional connectivity pattern in favor of more efficient and modularized utilization of the vast brain interconnections. State‐based statistical summary measures presented robust and significant group differences that also showed significant age‐related associations. The findings reported in this article support the idea of gradual developmental and aging brain state adaptation processes in different phases of life and warrant future research via lifespan studies to further authenticate the projected time‐resolved brain state trajectories. Abstract : We highlight the replicable time‐resolved developmental and aging functional brain patterns in a systematic evaluation of over 47, 000 youth and adult brains. Our study captured the most contrastive difference between the two life stages in a brain state that indicated coherent strengthening and modularization of functional coupling within the auditory, visual, and motor sub‐domains, supplemented by anticorrelation with other subdomains in adults, a pattern that was consistently less modular or absent in adolescents and presented a negative association with age in adults, thus indicating an overall inverted U‐shaped trajectory. This indicates greater synchrony, strengthening, modularization, and integration of the brain's functional connections beyond adolescence, and the gradual decline of this pattern during the healthy aging process.